Rat whisker motor cortex is subdivided into sensory-input and motor-output areas - Smith, Jared B.; Alloway, Kevin D. (Frontiers in Neural Circuits, 2013)
Rodent whisking is an exploratory behavior that can be modified by sensory feedback. Consistent with this, many whisker-sensitive cortical regions project to agranular motor (MI) cortex, but the relative topography of these afferent projections has not been established. Intracranial microstimulation (ICMS) evokes whisker movements that are used to map the functional organization of MI, but no study has compared the whisker-related inputs to MI with the ICMS sites that evoke whisker movements. To elucidate this relationship, anterograde tracers were placed in posterior parietal cortex (PPC) and in the primary (SI) and secondary (SII) somatosensory cortical areas so that their labeled projections to MI could be analyzed with respect to ICMS sites that evoke whisker movements. Projections from SI and SII terminate in a narrow zone that marks the transition between the medial (AGm) and lateral agranular (AGl) cortical areas, but PPC projects more medially and terminates in AGm proper. Paired recordings of MI neurons indicate that the region between AGm and AGl is highly responsive to whisker deflections, but neurons in AGm display negligible responses to whisker stimulation. By contrast, AGm microstimulation is more effective in evoking whisker movements than microstimulation of the transitional region between AGm and AGl. The AGm region was also found to contain a larger concentration of corticotectal neurons, which could convey whisker-related information to the facial nucleus. These results indicate that rat whisker motor cortex is comprised of at least two functionally distinct subregions: a sensory processing zone in the transitional region between AGm and AGl, and a motor output region located more medially in AGm proper.